Corporate governance and intellectual capital: Evidence from Universiti Teknologi Mara Melaka / Nor 'Asyiqin Abu, Akma Hidayu Dol@ Abdul Wahid and Ainol Sarina Ahmad Zazili - Abu, Nor 'Asyiqin; Dol@ Abdul Wahid, Akma Hidayu; Ahmad Zazili, Ainol Sarina (2012)
This study was conducted to examine the perception of the academicians towards intellectual capital (lC) and governance practice in UiTM. It also examines the factors to retain the qualified academicians and the relationship between IC and corporate governance (CG) in university. Analysis reveals that CG is the second factor influences the attraction and retention of the Ie. While the foremost factor that attracts academicians to join UiTM is the possibility of UiTM giving opportunity for their academic advancement. Furthermore, the analysis shows that UiTM have implemented a good governance. However, some improvement should be done in disclosure and transparency as well as integrity and trust. Finally, statistical result shows a positive relationship between IC and CG. It means, the higher the CG the higher the IC would be retained by the university. This result is further supported by 77 percent of the respondents who do not have any intention of leaving the university.